2007
DOI: 10.1016/j.bbrc.2007.07.092
|View full text |Cite
|
Sign up to set email alerts
|

The Dcr2p phosphatase destabilizes Sic1p in Saccharomyces cerevisiae

Abstract: Initiation of cell division is controlled by an irreversible switch. In Saccharomyces cerevisiae degradation of the Sic1p protein, an inhibitor of mitotic cyclin/cyclin-dependent kinase complexes, takes place before initiation of DNA replication, at a point called START. Sic1p is phosphorylated by multiple kinases, which can differentially affect the stability of Sic1p. How phosphorylations that stabilize Sic1p are reversed is unknown. Here we show that the Dcr2p phosphatase functionally and physically interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…In contrast, cells that were shifted to pheromone one step earlier, exhibited only a decline in the level of Sic1 (Figure 5B, step 17). This result points to Sic1 as the indicator for commitment, as previously suggested [31,32]. …”
Section: Resultssupporting
confidence: 83%
“…In contrast, cells that were shifted to pheromone one step earlier, exhibited only a decline in the level of Sic1 (Figure 5B, step 17). This result points to Sic1 as the indicator for commitment, as previously suggested [31,32]. …”
Section: Resultssupporting
confidence: 83%
“…Sic1 is a stoichiometric inhibitor of the B-type cyclins responsible for initiating replication (Schwob et al, 1994) and has been suggested to also play a role in cell cycle commitment (Pathak et al, 2007). To investigate the potential role of Sic1 at Start , we created a strain expressing Whi5-mCherry and Sic1-GFP from their endogenous loci.…”
Section: Resultsmentioning
confidence: 99%
“…Sic1 is targeted at multiple sites by several kinases such as Hog1 (Escote et al, 2004), Pho85 (Nishizawa et al, 1998), Ime2 (Sedgwick et al, 2006) and CK2 (Barberis et al, 2005b;Coccetti et al, 2006), but the effect of these phosphorylations on Sic1 stability is not fully understood. In addition, phosphorylations stabilizing Sic1 has been also reported, mediated by the phosphatase Cdc14 (Visintin et al, 1998) and Dcr2 (Pathak et al, 2007).…”
Section: Is Sic1 Part Of the Mechanism That Regulates Cell Cycle Coormentioning
confidence: 93%